LIBERALIZATION OF ISLAMIC EDUCATION - Muhlison, Fachruddin Azmi, (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract This discussion aims to increase understanding of the liberalization of education, which is a new formula for formulating the concept of education ideally. In the process, a teacher, for example, must understand the development of his students critically and sustainably. The method in this journal is to use a literature review. The Literature Review is a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities to develop a clear frame of mind from the formulation of the problem to be studied. Islamic education and educational liberalization attempt to change or reform the academic order so that the world of education is more advanced and gives a fresh colour so that Islamic education runs dynamically. Liberalization of education does not mean that it is free. Still, it must be in line with the values ​​of Islamic education, which must be adapted to the times so that it is not left behind to keep up with the development of the world of education. While in Islamic education, the essential concept that is by the values ​​in the Islamic vision is oriented not only to the world but also at the same time to achieve success, happiness, and benefit in the afterlife. Liberalization in Islamic education is the spread of liberal religious thought in Islamic educational institutions. The mode that occurs is intervention in the curriculum, providing scholarships and educational assistance, massive intellectual movements, spreading ideas and teachings that are liberal in the world of Islamic education. But actually, the principles of liberalism that give freedom to humans to freely express their thoughts and ideas are not contrary to Islam. Using reason to think is human nature. Therefore, it does not matter if freedom of thought is included in Islamic education, as long as it does not leave the religious authority of Muslims in the form of the Qur'an and hadith.